Real time wall conditioning with lithium powder injection in long pulse H-mode plasmas in EAST with tungsten divertor. (May 2019) - Sun, Z.; Maingi, R.; Hu, J.S.; Xu, W.; Zuo, G.Z.; Yu, Y.W.; Wu, C.R.; Huang, M.; Meng, X.C.; Zhang, L.; Wang, L.; Mao, S.T.; et al.
Highlights: A simple and real-time lithium powder injection technology was tested to facilitate 100 s long pulse H-mode operation on EAST, demonstrating the real-time injection of lithium powder is effective to solve the problem of lifetime limitation of coating film in present and future fusion devices. The outlined results indicate the real-time injection of lithium powder is contributed to wall conditioning recovery and help sustain stable long pulse H-mode operation by dramatically suppress impurity influx and control edge recycling on EAST with an ITER-like tungsten divertor. This research suggests that real-time lithium or the other low-Z material powder injection could be an effective method to improve the wall conditioning in future steady-state fusion devices. Abstract: Real-time lithium powder injection has been applied to long-pulse (>30 s) H-mode plasmas in EAST. This replenishes the active lithium surface that is routinely consumed by plasma-wall interactions. The real-time injection of Li powder into long H-mode discharges effectively suppresses impurity influx and controls recycling on EAST, with an ITER-like tungsten upper divertor. With lithium powder injection, the concentrations W, Mo, and C were reduced by 50% compared to ELMy H-mode discharges. During lithium injection, two effects play a role in the suppression of impurities influx: a reduced divertor temperature and heat flux and hence reduced erosion, and impurity trapping via deposition of a Li film onto plasma-facing surfaces. The 'fresh' injected lithium replenishes the film deposited during daily morning evaporation, restoring the wall's pumping capability. Thus, a measurable reduction in the global recycling coefficient was observed.